PENGARUH JENIS AGEN PENGENDAP ALAMI TERHADAP KARAKTERISTIK TAHU - Amelia Maharani; Dessy Kurniawati; Nita Aryanti (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2012)
Tofu is a popular soy processed food in Indonesia. The tofu made processing has done by the making ofusing sintetic coagulants. But general coagulant has some lacts which can influence the quality of tofu.Meanwhile the selection of natiral components as natural coagulant of tofu in Indonesia production itselfhave not been used. That is way in this research, the making of tofu will be done by using averrhoabilumbi, citrus acid, and chitosan as natural coagulants. It surrounds some steps that is coagulantspreparation, measurement of acidity of coagulants, preparation of soymilk, until preparation of tofu. Theproximate analysis of tofu is yield of tofu analysis, crude protein analysis and moisture content analysis.This research show that the use of comersiil coagulants (CaSO4) results lower yield than naturalcoagulants. The effects of additon of natural coagulants in making process of tofu, which naturalcoagulants each other has positive effects and negative effects itself, but generally the use of naturalcoagulants has positive effects than comersiil coagulants CaSO4. In next research it will be better to doanalysis of parameter of tofu texture besides hardness, they are cohessiveness, springiness, andchewiness to get more complete discussion. It need too add the other variable in knowing the effects ofthe quality of tofu like pH, temperature, mixing speed, coagulation time and many more.